2017
DOI: 10.4103/0972-9941.199609
|View full text |Cite
|
Sign up to set email alerts
|

Transperitoneal laparoscopic nephrectomy in acute Grade 4 renal trauma with literature review and a note on some unusual complications

Abstract: Most renal traumas are successfully managed conservatively. Grade 4 and 5 trauma, however, can require nephrectomy which is almost always by laparotomy and laparoscopic nephrectomy (LN) is still considered contraindicated in acute trauma setting. We report successful transperitoneal LN in an acute grade 4 renal trauma with retroperitoneal haematoma, extensive parenchymal devascularisation and urinary extravasation though retroperitoneoscopic nephrectomy in trauma has been reported recently. However, we believe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Design of included studies: 3 articles were case reports and 1 was a case series. [11][12][13][14] Region of study origin: Included studies were conducted in Australia, Italy, India and China. [11][12][13][14]…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Design of included studies: 3 articles were case reports and 1 was a case series. [11][12][13][14] Region of study origin: Included studies were conducted in Australia, Italy, India and China. [11][12][13][14]…”
Section: Resultsmentioning
confidence: 99%
“…Three studies only reported on one patient as they were case reports, and one study conducted by Wang et al reported on three patients. [11][12][13][14]…”
Section: Sample Sizementioning
confidence: 99%
See 3 more Smart Citations